Cyanidin-3-O-Glucoside Protects against 1,3-Dichloro-2-Propanol-Induced Reduction of Progesterone by Up-regulation of Steroidogenic Enzymes and cAMP Level in Leydig Cells - Sun, Jianxia; Xu, Wei; Zhu, Cuijuan; Hu, Yunfeng; Jiang, Xinwei; Ou, Shiyi; Su, Zhijian; Huang, Yadong; Jiao, Rui; Bai, Weibin (Frontiers in Pharmacology, 2016)
1,3-Dichloro-2-propanol (1,3-DCP) is a food processing contaminant and has been shown to perturb male reproductive function. Cyanidin-3-O-glucoside (C3G), an anthocyanin antioxidant, is reported to have protective effects on many organs. However, it remains unclear whether C3G protects against chemical-induced reproductive toxicity. The present study was therefore to investigate the intervention of C3G on 1,3-DCP-induced reproductive toxicity in R2C Leydig cells. Results demonstrated that C3G inhibited the 1,3-DCP-induced cytotoxicity and cell shape damage with the effective doses being ranging from 10-40 μmol/L. In addition, 1,3-DCP (2 mmol/L) exposure significantly increased the ROS level and mitochondrial membrane potential (MMP) damage ratio, leading to a decrease in progesterone production, while C3G intervention reduced the ROS level, and increased the progesterone production after 24 h treatment. Most importantly, C3G intervention could up-regulate the cyclic adenosine monophosphate (cAMP) level and protein expression of steroidogenic acute regulatory protein (StAR) and 3β-hydroxysteroid dehydrogenase (3β-HSD). It was concluded that C3G is effective in reducing 1,3-DCP-induced reproductive toxicity via activating steroidogenic enzymes and cAMP level.